(untitled) (Itinera, 2014)
The grotesque can then be seen as the aesthetic effect generated by the clash between different categories and genres of representation. The dramatic function of the page Oscar in Un ballo in maschera arises from the cross of two different triangles: the dramatic positions tieing him with Cherubino (Nozze di Figaro) and Smeton (Anna Bolena), and the vocal triangle binding him to Abigaille (Nabucco) and Gilda (Rigoletto). In this case, infact, Verdi declines, the version nor heroic nor pathetic but grotesque of belcanto. For his vocality, Oscar is in an eccentric position with respect to the line that binds the operatic pages such as Cherubino and Smeton. This line, however, constitutes the reference horizon on which he projects himself, according to well established Nineteenth-Century expectations of the spectators.